Innovation in Financial Management: Opportunities and Challenges in Improving Organizational Performance - Hasanudin Hasanudin (Sean Institute, 2024)
This research explores innovation in financial management as an effort to improve organizational performance. In the context of increasingly tight business competition, innovation is not only applied to products or services, but also in management systems and processes, including financial management. This research aims to identify the opportunities and challenges offered by financial innovation, such as financial technology (fintech), big data analytics and business process automation. This research uses a qualitative approach with descriptive methods. The research results show that innovation in financial management can have a positive impact on organizational performance. The integration of financial technology, the use of big data, and the automation of financial processes effectively improve operational efficiency, enable more timely decision making based on data, and optimize the use of resources. Although challenges such as initial investment costs and employee resistance to change may arise, effective communication and proper training can overcome these obstacles, ensuring successful adoption of the innovation. Thus, research confirms the importance of integrating innovation in financial management as a strategy to improve organizational performance and competitiveness in an ever-changing business environment.